STUDENTS' INDEPENDENT WORK ON THE METHODOLOGY OF TEACHING LITERATURE (American Journal of Interdisciplinary Research and Development, 2024)
The article discusses the problem of organizing independent work in literature lessons aimed at studying various methods of teaching literature to students. It provides various approaches that can be used to effectively study literature, as well as an analysis of their effectiveness in improving student learning outcomes.